Identifikasi Karakteristik Siswa Dalam Pembelajaran Di Kelas V SDN 47 Bau-Bau - Wa Ode Delsi Mecriyani; Janihu Ali; Haliadi Haliadi; Tiyani, Tiyani; Sri Mulyani; Delfi Astian6 (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Learning in elementary schools needs to consider student characteristics so that the learning process is effective and meets students' needs. This study aims to identify the characteristics of fifth-grade students at SDN 47 Baubau, including learning styles, motivation, cognitive abilities, and socio-emotional aspects. The study used a qualitative descriptive approach with 28 students and one class teacher as subjects. Data collection techniques included observation, interviews, and questionnaires, while analysis was conducted through reduction, presentation, and drawing conclusions. The results showed that visual and kinesthetic learning styles dominated (46% and 39%, respectively), while auditory students only made up 15%. Learning motivation was mostly moderate to high, with some students showing a lack of self-confidence. Cognitive abilities were heterogeneous; 32% quickly understood the material, while 68% required more intensive guidance. The socio-emotional aspect showed that most students were able to work together, but still needed guidance in communication and responsibility. These findings are consistent with studies by Jampel (2016) and Fianto et al. (2025) regarding variations in learning styles, as well as Salamah et al. (2023) and Samrotul Puadah et al. (2024) regarding learning motivation. The research emphasizes the importance of implementing differentiation strategies, contextual learning, and collaborative learning to ensure the holistic development of each student. These results are expected to serve as a basis for teachers in designing adaptive, effective, and student-centered learning.